2008
DOI: 10.1111/j.1440-1843.2008.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis—results from a Japanese nationwide epidemiological survey using individual clinical records

Abstract: Nationwide epidemiological survey of patients with idiopathic pulmonary fibrosis using clinical personal records in Japan OHNO S, NAKAYA T, BANDO M, SUGIYAMA Y. Respirology 2008; 13: 926-928

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 6 publications
1
25
1
Order By: Relevance
“…Our study is the first to present the prevalence of typical CPFE patterns on chest CT images in patients with MPA. Although the exact prevalence of CPFE in the Japanese population is not known, the prevalence of typical CPFE patterns in MPA patients in our study (4%) is much higher than that of idiopathic interstitial pneumonias estimated in the Japanese population (0.0023-0.0034%) (33,34).…”
Section: Discussioncontrasting
confidence: 66%
“…Our study is the first to present the prevalence of typical CPFE patterns on chest CT images in patients with MPA. Although the exact prevalence of CPFE in the Japanese population is not known, the prevalence of typical CPFE patterns in MPA patients in our study (4%) is much higher than that of idiopathic interstitial pneumonias estimated in the Japanese population (0.0023-0.0034%) (33,34).…”
Section: Discussioncontrasting
confidence: 66%
“…For example, the contrast between the proportion of deaths due to 'unspecified' interstitial lung disease in Japan (70-75%) and elsewhere (10-20%) warrants further exploration. Previous literature has suggested a lower incidence of IPF in East Asia (19,20) although this likely relates to sampling of insurance databases featuring mainly severe disease. Assessment of data from other countries in East…”
Section: Discussionmentioning
confidence: 96%
“…Different studies have reported a varying prevalence of IPF from 1.25 to 27.9 cases per 100,000 (5)(6)(7)(8)(9)(10)(11)(12), as shown in Figure 1. A study in the United Kingdom estimated that the incidence of IPF increased by 11% annually from 1991 to 2003 (13).…”
Section: General Condition and Epidemiologymentioning
confidence: 98%